1984
DOI: 10.1002/jmv.1890140312
|View full text |Cite
|
Sign up to set email alerts
|

The heat sensitivity of hepatitis A virus determined by a simple tissue culture method

Abstract: A method for estimating residual infectious hepatitis A virus (HAV) after heat treatment of suspensions of the virus was devised. It made use of a readily maintained cell line (FRhK-4) in which the rate of release of HAV antigen into the tissue culture medium was directly proportional to the size of the inoculum. Loss of viral infectivity after heating could be estimated by inoculating heat-treated HAV suspensions into cell monolayers and measuring antigen released from the cultures during 5 weeks of incubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 9 publications
0
38
0
2
Order By: Relevance
“…In order to evaluate the effects of food matrix composition on thermal inactivation, the levels of resistance of HAV were compared in several food samples. Thermal inactivation studies for HAV have involved cell culture medium, spinach, shellfish, mussels, clams, cockles, and milk; reported D values for HAV in the range of 50 to 100°C were 0.01 to 385 min (26,27,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). According to the product description, the composition of the turkey deli meat included sodium (10 mg/g), fat (0.8%), carbohydrates (1.7%), protein (19%), and moisture (77%).…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the effects of food matrix composition on thermal inactivation, the levels of resistance of HAV were compared in several food samples. Thermal inactivation studies for HAV have involved cell culture medium, spinach, shellfish, mussels, clams, cockles, and milk; reported D values for HAV in the range of 50 to 100°C were 0.01 to 385 min (26,27,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). According to the product description, the composition of the turkey deli meat included sodium (10 mg/g), fat (0.8%), carbohydrates (1.7%), protein (19%), and moisture (77%).…”
Section: Resultsmentioning
confidence: 99%
“…2-log reduction in virus titer, respectively (18). Complete inactivation of HAV was only achieved at 98ЊC for 1 min (11).…”
Section: Discussionmentioning
confidence: 99%
“…Frosner (1982) (1952) demonstrated that ice cream, cream and milk can exert protective effects on poliovirus when exposed to heat. Parry & Mortimer (1984) found that the stability of HAV was increased when suspended in milk. The steaming or immersion in boiling water of shellfish such as cockles is intended to render them safe for the consumer.…”
Section: Discussionmentioning
confidence: 99%